Copper nanoparticles embedded in a polyimide film for non-volatile memory applications - Gupta, Raju Kumar (2013)
The charge storage and retention characteristics of a nanoparticle-laden thin polyimide film were investigated for application in non-volatile memory devices. Well-dispersed and uniform sized metallic copper nanoparticles (CuNPs) were formed as embedded entities within the confines of polyimide film that was cast from solution. The nanoparticle-containing films were characterized by X-ray photoelectron spectroscopy, atomic force and scanning electron microscopies. Capacitance–voltage measurements showed that the embedded CuNPs functioned as a floating gate in metal–insulator–semiconductor-type capacitor and exhibited a large hysteresis window of 1.52 V. C–t measurements conducted after applying a charging bias of 5 V showed that the charge was retained beyond 20,000 s. The technique holds promise for developing low-cost processes for memory devices that employ relatively inexpensive materials, and yet demonstrate very good performance.